Longevitas dan Efikasi Pelet Trichoderma harzianum terhadap Sclerotium rolfsii Penyebab Penyakit Layu pada Tanaman Tomat (Solanum lycopersicum L.) - Juni Safitri Muljowati; Uki Dwiputranto; Iman Budisantoso (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2014)
Trichoderma harzianum is one of the antagonist fungi that can be used as a biofungicide to control soil-borne pathogens such as Sclerotium rolfsii, the cause of wilt isease of tomato. To ease the application of T.harzianum fungi in the field, it should be prepared a formulation in form of pellet. The longevity of T.harzianum pellet is determined by the viability of T.harzianum fungi contained in it, whereas the efication/ effectivity of T.harzianum pellet is determined by the longevity of the pellet.  The objectives of this study are to investigate the interaction between storage period and application dosages in controlling wilt disease of tomato;  and the dosage and storage period of T.harzianum on the effectiveness in controlling wilt disease of tomato. The experiment was carried out experimentally by using a Completely Randomized Design (CRD) in a factorial pattern. The first factors were storage period (W) consisted of 5 levels, i.e. 0, 3, 6, 9, and 12 weeks; the second factors were theapplication dosages (D) consisted of 6 levels, i.e. 0, 25, 50, 75, 100, and 125 grams. They were replicated 3 times each. The viability observation of T.harzianum was completed at the end of storage period of the pellets, the disease occurence and severity was since the 4th day after inoculation with 4 day interval until the tomato plant produced flowers. Research result showed that the interaction between storage period and different application dosages of T.harzianum pellets has influenced the increase of wilt disease control of tomato. Furthermore, storage period of 6 weeks and T.harzianum application of 50 g were the most effective in controlling wilt disease of tomato.